Development and Testing of a Communication Intervention to Improve Chronic Pain Management in Primary Care: A Pilot Randomized Clinical Trial. Issue 10 (25th October 2022) - Henry, Stephen G.; Fenton, Joshua J.; Campbell, Cynthia I.; Sullivan, Mark; Weinberg, Gary; Naz, Hiba; Graham, Wyatt M.; Dossett, Michelle L.; Kravitz, Richard L.
Abstract : Objectives: Effective communication skills are essential for optimally managing chronic pain and opioids. This exploratory, sequential mixed methods study tested the effect of a novel framework designed to improve pain-related communication and outcomes. Methods: Study 1 developed a novel 5-step framework for helping primary care clinicians discuss chronic pain and opioids with patients. Study 2 pilot tested an intervention for teaching this framework using standardized patient instructors—actors trained to portray patients and provide immediate clinician feedback—deployed during regular clinic hours. Primary care physicians were randomized to receive either the intervention or pain management recommendations from the Centers for Disease Control and Prevention. Primary outcomes were pain-related interference at 2 months and clinician use of targeted communication skills (coded from transcripts of audio-recorded visits); secondary outcomes were pain intensity at 2 months, clinician self-efficacy for communicating about chronic pain, patient experience, and clinician-reported visit difficulty. Results: We enrolled 47 primary care physicians from 2 academic teaching clinics and recorded visits with 48 patients taking opioids for chronic pain who had an appointment scheduled with an enrolled physician. The intervention was not associated with significant changes in primary or secondary outcomes other than clinician self-efficacy, which was significantly greater in the intervention group. Discussion: This study developed a novel framework and intervention for teaching clinician pain-related communications skills. Although the intervention showed promise, more intensive or multicomponent interventions may be needed to have a significant impact on clinicians' pain-related communication and pain outcomes.